Rapid Fluorescence Polarization Immunoassay for Highly Sensitive Detection of 2,4,6-Trinitrotoluene - Lu, Wenzong; Ni, Yuan; Jia, Guangfeng; Pan, Haixian; Zhao, Chen (Asian Journal of Chemistry, 2014)
Detection of explosives is of great significance in public security programmer and environmental science. In the present work, a fluorescence polarization immunoassay based on a monoclonal antibody for the detection of 2,4,6-trinitrotoluene was established and optimized. Fluorescein-labeled (tracer) was synthesized and purified by column chromatography. The immunoassay exhibited excellent sensitivity for the detection of 2,4,6-trinitrotoluene with good stability. The detection limit was 5 μg mL-1, within a response time of 4 min. The cross-reactivity of the method to 1,3,5-trinitrohexahydro-1,3,5-triazine, 2,4,6-trinitrophenol, 2,4,6-trinitrobenzoic acid, 2-nitrotoluene and 2,4-dinitrotoluene, were very low (cross-reactivity < 0.01 %). The method developed is characterized by high specificity and reproducibility (coefficients of variance ranged from 2.7-6.5 % for interassay and from 1.6-4.4 % for intra-assay). The relative error value was less 1 % in assay of simulating environmental sample. The fluorescence polarization immunoassay method can be applied to the screening of environmental sample for 2,4,6-trinitrotoluene without complicated operation.